Embryo biotechnologies in sheep: Achievements and new improvements. (27th April 2022) - Falchi, Laura; Ledda, Sergio; Zedda, Maria T.
Abstract: To date, large‐scale use of multiple ovulation and embryo transfer (MOET) programmes in ovine species is limited due to unpredictable results and high costs of hormonal stimulation and treatment. Therefore, even if considered reliable, they are not fully applicable in large‐scale systems. More recently, the new prospects offered by in vitro embryo production (IVEP) through collection of oocytes post‐mortem or by repeated ovum pick‐up from live females suggested an alternative to MOET programmes and may be more extensively used, moving from the exclusive research in the laboratory to field application. The possibility to perform oocytes recovery from juvenile lambs to obtain embryos (JIVET) offers the great advantage to significantly reduce the generation interval, speeding the rate of genetic improvement. Although in the past decades several studies implemented novel protocols to enhance embryo production in sheep, the conditions of every single stage of IVEP can significantly affect embryo yield and successful transfer into the recipients. Moreover, the recent progresses on embryo production and freezing technologies might allow wider propagation of valuable genes in small ruminants populations and may be used for constitution of flocks without risks of disease. In addition, they can give a substantial contribution in preserving endangered breeds. The new era of gene editing might offer innovative perspectives in sheep breeding, but the application of such novel techniques implies involvement of specialized operators and is limited by relatively high costs for embryo manipulation and molecular biology analysis.